HUBUNGAN GAYA KEPEMIMPINAN MANDOR PANEN DAN MOTIVASI KERJA PEMANEN DENGAN KINERJA PEMANEN DI PT PERKEBUNAN NUSANTARA VII UNIT KEBUN KELAPA SAWIT (UKKS) REJOSARI NATAR, LAMPUNG SELATAN - Faridatu Cholqiyati Alimah; Wuryaningsih Dwi Sayekti; Achdiansyah Soelaiman (Lampung University, 2016)
This research aims to know the harvest foreman leadership style, motivation and performance level of harvesters, relation between harvest foreman leadership style and performance of harvester, relation between work motivation of harvesters and performance of harvester, and relation between harvest foreman leadership style and work motivation of harvesters. This research was conducted by survey method at PT Perkebunan Nusantara VII UKKS Rejosari Natar of South Lampung. The research samples consisted of 50 people who were drawn from the population by proporsional random sampling. The data was collected from June to July 2015 and analyzed by descriptive and rank spearman correlation analysis. The results showed as follows. The harvest foreman leadership style was democratic leadership style. The work motivation of harvesters was in high category. The performance of harvesters was in high category. The leadership style of harvest foreman was related to the performance of harvesters. The work motivation of harvesters was related to the performance of harvesters. The leadership style of harvest foreman was related to the motivation of harvesters.Key words: leadership style, performance of harvester, work motivation